Inventing the Minoans: Archaeology, Modernity and the Quest for European Identity - Papadopoulos, John K. (Journal of Mediterranean Archaeology, 2007)
This study explores the modern history of Minoan culture and the myth of Minoan archaeology. Emerging from the cultural milieu of the late 19th and early 20th centuries, the genesis of this culture formed in the mind of Arthur Evans soon after he began excavations at Knossos in 1900. By 1930, he had transformed the site previously excavated by Minos Kalokairinos and earlier known as Tou Tseleve he Kephala and Ta Pitharia into the so-called Palace of Minos, and from poorly preserved ruins into a brightly painted, multi-storied, concrete vision of the past. After Evans’s death, the restored palace became one of the most visited archaeological sites in the world and, in the process, the restoration assumed its own historical identity and became a major problem of conservation. Evans was the first not only to restore a monument to such an extent, but also to use actual archaeological remains as a medium of expression. Beyond giving posterity his vision of the past, Evans was to have a much greater influence on archaeological thought than is currently conceded. Evans viewed his Minoans as the first great European culture, but it was his disciple, V. Gordon Childe, who was to apply the concept of an archaeological culture systematically in his The Dawn of European Civilization (1925), thereby making it a working tool for all European archaeologists. At the brink of modernity, archaeology became entangled with a quest for European identity, and the legacy of that time continues to exert its influence on the present.